Early Arthritis: Translation from Experiences with RA to Children with JIA - Vinall, Maria (MD Conference Express, 2006)
When should primary care physicians refer patients with suspected juvenile idiopathic arthritis (JIA) and what tests should they perform? This article discusses new ways to predict early outcomes for patients with JIA.